A problemática da autonomia e da heteronomia nacional brasileira a partir dos intelectuais finisseculares Manoel Bomfim, Oliveira Lima e Graça Aranha - Maciel, Renata Baldin (2019)
This investigation offers an Intellectual History approach and aims to explore the theoretical and methodological scopes of the area in order to verify some conceptions related to autonomy and heteronomy in the works of the Brazilian academics Manoel Bomfim, Oliveira Lima and Graça Aranha. The focus of the authors offer answers about civilization, identity and race, concepts presented to understand how the Brazilian Fin-de-siècle generation was thinking autonomy, heteronomy and nation in a context of changes, especially with the Proclamation of the Republic. The hypothesis of this thesis shows that the connection between autonomy and heteronomy was temporally built and applied to the national matters to compose those intellectuals’ interpretation of the world, specially concerning to the space of experience and horizon of expectation. Therefore, autonomy and heteronomy elucidate the disorientation of the Brazilian Fin-de-siècle generation from 1890 to 1920 before the perception of the backwardness, maladjustment and incompleteness of the nation. This thesis is divided in three chapters: the first presents introductory aspects and discusses the characteristic elements of the Brazilian intellectual context of the time, as well as a brief resumption of recent publications about those intellectuals. The second chapter focuses on the European, Iberian and American civilizational models to demonstrate how they have configured Brazilian national identity. The third chapter follows the identity discussions of the previous chapter, emphasizing the racial aspect in the process of definition of the Brazilian national being and how it was linked to the autonomy and heteronomy of the nation. Education also appears in this last chapter associated to the idea of utopia in the constitution of the future.